Developing emergent bibliteracy: guiding principles for instruction - López, Alexis; Sosa Ortíz, Yolanda (Colombian Applied Linguistics Journal, 2004)
We are advocating for the adoption of simultaneous emerging biliteracy programs in binational/bilingual schools in Colombia. The adoption of such programs as an influence on the teacher education institutions across the country. We must prepare teachers to respond the technological era of the twenty firts century in wich information is accessible in different languages at the touch of a button. In this article we present five principles for emergent bibliteracy instruction. After providing these principles we offer implications for teachers, educators and prospective teachers.